Online teaching and learning: Experiences of students in a nursing college during the onset of COVID-19 - Lebogang L. Molefe; Nkhensani F. Mabunda (AOSIS, 2022)
Background: The world has entered the Fourth Industrial Revolution. Utilisation of technology is inevitable. For the past years, the coronavirus disease 2019 (COVID-19) pandemic has halted normal operations, including in the physical classroom for nursing students. Students and facilitators had to move to a remote way of teaching and learning, utilising online teaching and learning. However, students and facilitators were not ready to use online teaching and learning. This not only resulted in numerous challenges, but also became an eye-opener for best practices and intervening strategies. Objectives: To explore and describe experiences of students in a nursing college with regard to online teaching and learning during the onset of the COVID-19 pandemic. Method: A qualitative, exploratory, descriptive and contextual research design was adopted. A purposive, nonprobability sampling approach was used to select participants from second year, third year and fourth year. First-year student nurses were excluded because they did not commence with classrooms at that time. Results: Seven themes emerged, namely knowledge, confidence, training, equipment, clinical exposure, course extension and flexibility, and all themes had subthemes. Conclusion: It is evident that students had more negative experiences during online teaching and learning than positive experiences. Contribution: The study contributed enormously to teaching and learning of student nurses in nursing colleges as its results can be used to improve nursing colleges with regard to online teaching and learning.